A Different Approach of Dizziness in Older Patients: Away from the Diagnostic Dance between Patient and Physician - Maarsingh, Otto R.; Stam, Hanneke; van der Horst, Henriëtte E. (Frontiers in Medicine, 2014)
Although the aetiology of dizziness in older patients differs significantly from that of younger patients, most guidelines on dizziness advocate the same diagnosis-oriented approach for all patients regardless of their age. However, this diagnosis-oriented approach may be insufficient for older patients presenting with dizziness in general practice, because 1) general practitioners are often not able to identify an underlying cause of dizziness, 2) general practitioners regularly identify causes of dizziness that cannot be treated, and 3) general practitioners may identify causes of dizziness for which treatment is available but not desirable. In this article, the authors present a simultaneous diagnosis- and prognosis-oriented approach for older dizzy patients. This approach may enable general practitioners to improve their care for a voluminous group of impaired older patients, even if a diagnosis is not available (yet).